Effects of neuro-linguistic programming course on job stress, positive organizational behavior and job motivation in physical education teachers - Anjomshoa, M.R.; Fahim Devin, Y.; Esmailzadeh, M.R.; Keshtidar, M. (Pedagogy of physical culture and sports, 2020)
Purpose: The purpose of this study was to investigate the effects of a neuro-linguistic programming course on job stress, positive organizational behavior and job motivation among physical education teachers of Khorasan Razavi province of Iran. Material: The statistical population of the study consisted 150 physical education teachers of Khorasan Razavi province. 40 physical education teachers were selected as statistical sample. At first, the questionnaires of job stress of Steinmetz (2002), Luthans Psychological Capital questionnaire (2007) and Hackman job motivation questionnaire (1976) were administered to the subjects and then the subjects received the presented protocol. At the end of the course questionnaires were re-presented. Data were analyzed using repeated measures ANOVA and Bonferroni post hoc test at 5% error level. Results: The results showed that neuro-linguistic programming had a significant increase in job motivation and positive organizational behavior and a significant decrease in teachers' job stress (P<0.001). There was no significant change in job motivation, positive organizational behavior and job stress in the control group (P <0.05). Conclusions: According to the findings, it can be concluded that to increase the job motivation, these course can be used and affect the motivation and job stress of the employees.